Foot‐related health care use in patients with rheumatoid arthritis in an outpatient secondary care center for rheumatology and rehabilitation in the Netherlands: A cohort study with a maximum of fifteen years of followup. Issue 2 (30th January 2013) - Marsman, Anneke F.; Dahmen, Rutger; Roorda, Leo D.; van Schaardenburg, Dirkjan; Dekker, Joost; Britsemmer, Karin; Knol, Dirk L.; van der Leeden, Marike
Abstract Objective To describe foot‐related health care use over time in a cohort of rheumatoid arthritis (RA) patients in an outpatient secondary care center for rheumatology and rehabilitation in The Netherlands. Methods A total of 1, 087 patients with recent‐onset RA from 1995 to September 2010 were included in the study. All foot‐related visits to the podiatrist, rehabilitation physician, orthopedic surgeon, and the multidisciplinary foot‐care clinic were registered and described. Logistic regression techniques for longitudinal data were used to analyze the course of foot‐related health care use. Results A total of 32.9% of patients visited a podiatrist in secondary care during the course of their disease. For most patients, a visit to the podiatrist took place during the first year after diagnosis. This was followed by a significant decrease in visits in the ensuing years. Nine percent of patients visited the rehabilitation physician with foot symptoms, with peak prevalences between year 10 and 11 and during year 14 of followup. The orthopedic surgeon was visited by 5.3% of patients with foot symptoms, with a significant increase in visits over time. The multidisciplinary foot‐care clinic was visited by 7.5% of patients. This was significantly associated with visits to the rehabilitation physician. Conclusion In an outpatient secondary care center in The Netherlands, RA patients with foot symptoms visited the podiatrist in an early stage of the disease. When foot symptoms worsened, patients visited the rehabilitation physician, who subsequently referred patients to the multidisciplinary foot‐care clinic for therapeutic footwear. The orthopedic surgeon was the final step in the management of foot symptoms.